Quantitative Measurement of Flavonoid Content of Kecapi Leaves (Sondoricum koetjape Merr.) - Alfatiha, Rahma Tiara; Nisa, Fakhrotun (Hydrogen: Jurnal Kependidikan Kimia, 2026)
The kecapi leaf plant (Sondoricum koetjape Merr.) is a plant that has efficacy as a traditional medicine such as trating roundworms reducing fever. The kecapi leaf plant has been known to contain flavonoid, phenol, tannin and saponin compounds with properties as free radical scavengers. This study aims to determine the total flavonoid content of kecapi leaf extract. This study is experimental in nature. The sample used was kecapi leaves originating from Ckalahi Village, Cinangka Anyer District, Serang Regency, Banten. Determination of total flavonoid content was carried out using a UV-Vis Spectrophotometer. The result of this study obtained flavonoid levels in mg/L units of 5.4845 mg/L, while the flavonoid concentration in percent (%) units was obtained of 10.97% and in mg QE/g units the total flavonoid obtained were 109.6899 mg QE/g, while the qualitative test indicated that it contained flavonoid, phenol, tannin and saponin compounds.